Analisa Peran HRIS Terhadap Kinerja Karyawan PT. Kabana Textile Industries - Mujibul Hakim; Aria Mulyapradana; Muhammad Syaqiq (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2022)
This study has tested the HRIS (human resource information system) variables and the performance of employees at PT. Kabana Textile Industries. The research method uses a descriptive quantitative approach, processing data using the SPSS application, data collection techniques using questionnaires and research instruments with a Likert scale. The data analysis technique is through validity, reliability and multiple regression analysis with 125 employees as respondents. The results of the validity and reliability test showed that the application of the HRIS variable, job satisfaction and employee performance variables was valid and reliable. There is a significant relationship between the HRIS variable and the employee performance variable with a positive coefficient value of 0.515. The results showed that the HRIS variable was able to support the improvement of employee performance in. Employee performance is considered good with employees who have responsibility for the work given by the leadership.